Stimulating Spinal Cord Function Through Rhythmic Gymnastics for Children Aged 5-6 Years - Agusti, Septa; Safitri, Azizah Nur; Kurniawati, Pepi; Leriantika, Salsabilah (PT Ilmu Inovasi Nusantara, 2024)
The spinal cord is a collection of nerve fibers located along the spine, stretching from the bottom of the brain to the lower back. part of the body which is also called the medical term finalistic medulla. As is known, the brain is the central organ that gives orders to other body organs, even the smallest cells in the body. Meanwhile, the spinal cord is a bridge that connects messages from the brain to the body parts and vice versa. Often the spinal cord is not stimulated properly and this has a big impact on its development, so in order for the spinal cord to function well it needs to be stimulated in one way, namely rhythmic gymnastics. With rhythmic gymnastics, the child will be free to move his body while following the rhythm so that the child's spinal cord or spinal cord can move well.